2014
DOI: 10.1007/s10899-014-9494-x
|View full text |Cite
|
Sign up to set email alerts
|

At-Risk/Problematic Shopping and Gambling in Adolescence

Abstract: Elevated levels of both pathological gambling (PG) and problem shopping (PS) have been reported among adolescents, and each is associated with a range of other negative health/functioning measures. However, relationships between PS and PG, particularly during adolescence, are not well understood. In this study, we explored the relationship between different levels of problem-gambling severity and health/functioning characteristics, gambling-related social experiences, gambling behaviors and motivations among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
1
12
1
Order By: Relevance
“…Only the participants who responded to all MAGS items were stratified into gambling groups. As in prior studies (Yip et al 2014; Potenza et al 2011; Rahman et al 2012; Slavin et al 2013), participants who reported past-year gambling but did not endorse any DSM-IV diagnostic criteria for pathological gambling were classified as having low-risk gambling. Participants who endorsed one to two diagnostic criteria were classified as having at-risk gambling, while those who endorsed three or more were classified as having problem/pathological gambling.…”
Section: Methodsmentioning
confidence: 99%
“…Only the participants who responded to all MAGS items were stratified into gambling groups. As in prior studies (Yip et al 2014; Potenza et al 2011; Rahman et al 2012; Slavin et al 2013), participants who reported past-year gambling but did not endorse any DSM-IV diagnostic criteria for pathological gambling were classified as having low-risk gambling. Participants who endorsed one to two diagnostic criteria were classified as having at-risk gambling, while those who endorsed three or more were classified as having problem/pathological gambling.…”
Section: Methodsmentioning
confidence: 99%
“…these conditions [22,23]. It has previously been established in research on the association of problem gambling and shopping addiction that adolescents with problematic gambling are more likely to suffer from anxiety which could only be relieved by shopping [24]. Problematic gaming has also been found to be positively correlated with problem gambling [25].…”
Section: Introductionmentioning
confidence: 97%
“…The most appropriate thresholding for PIU has been debated ( 17 ), and data suggest that the more stringent thresholding used in diagnostic criteria for behavioral as compared to substance addictions may miss clinically relevant groups ( 18 ). Given that youth may have their developmental trajectories may be negatively impacted by engagement in sub-diagnostic engagement in risk behaviors, we opted to investigate PIU using a relatively liberal threshold (which we term at-risk/PIU, or ARPIU), as we have in prior studies ( 19 22 ).…”
Section: Introductionmentioning
confidence: 99%